2022
DOI: 10.3389/fmicb.2022.1005480
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic cell surface display system of PETase as a sustainable biocatalyst for PET degradation

Abstract: Remarkably, a hydrolase from Ideonella sakaiensis 201-F6, termed PETase, exhibits great potential in polyethylene terephthalate (PET) waste management due to it can efficiently degrade PET under moderate conditions. However, its low yield and poor accessibility to bulky substrates hamper its further industrial application. Herein a multigene fusion strategy is introduced for constructing a hydrophobic cell surface display (HCSD) system in Escherichia coli as a robust, recyclable, and sustainable whole-cell cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Surface display systems for PETase show little loss of enzyme activity over 7 days [ 28 , 44 ], whereas soluble PETase loses activity more rapidly. We compared the activity of surface displayed MHETase to soluble purified MHETase after incubating for up to 12 days at room temperature in phosphate buffer.…”
Section: Resultsmentioning
confidence: 99%
“…Surface display systems for PETase show little loss of enzyme activity over 7 days [ 28 , 44 ], whereas soluble PETase loses activity more rapidly. We compared the activity of surface displayed MHETase to soluble purified MHETase after incubating for up to 12 days at room temperature in phosphate buffer.…”
Section: Resultsmentioning
confidence: 99%
“…The PET degradation efficiency of the co-display systems was significantly increased compared to E. coli cells that solely displayed Fast-PETase on the surfaces, proving the feasibility and utility of co-display approach with E. coli system. Because of the use of different PET materials and PETase enzymes for degradation tests (Chen et al 2022 ; Gercke et al 2021 ; Jia et al 2022 ; Zhu et al 2022 ), it was impossible for us to make a direct comparison with other reported systems. Nevertheless, over 15% degradation of amorphous PET in 24 h was the highest value to date.…”
Section: Discussionmentioning
confidence: 99%
“…1 A). To overcome the limitations of using free enzymes, such as instability and time-consuming purification process, various whole cell systems have been constructed for PET biodegradation using the PETases from different sources (Chen et al 2022 , 2020 ; Gercke et al 2021 ; Jia et al 2022 ; Zhu et al 2022 ). However, the efficiency of PET biodegradation by these systems is still lower than realistic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Surface display systems for PETase show little loss of enzyme activity over 7 days [25,40], whereas soluble PETase loses activity more rapidly. We compared the activity of surface displayed MHETase to soluble purified MHETase after 12 days at room temperature in phosphate buffer.…”
Section: The Mhetase Whole-cell Catalyst Is Stable To Alkaline Ph Tem...mentioning
confidence: 99%